Scientific instrument Femtosecond X‐ray Experiments (FXE): instrumentation and baseline experimental capabilities. (9th August 2019) - Galler, Andreas; Gawelda, Wojciech; Biednov, Mykola; Bomer, Christina; Britz, Alexander; Brockhauser, Sandor; Choi, Tae-Kyu; Diez, Michael; Frankenberger, Paul; French, Marcus; Görries, Dennis; Hart, Matthiew; et al.
Abstract : The Femtosecond X‐ray Experiments scientific instrument is a versatile instrument for ultrafast pump–probe X‐ray absorption, emission and scattering experiments at the European XFEL; the instrumentation, commissioning results and operation performance status are presented. Abstract : The European X‐ray Free‐Electron Laser (EuXFEL) delivers extremely intense (>10 12 photons pulse −1 and up to 27000 pulses s −1 ), ultrashort (<100 fs) and transversely coherent X‐ray radiation, at a repetition rate of up to 4.5 MHz. Its unique X‐ray beam parameters enable novel and groundbreaking experiments in ultrafast photochemistry and material sciences at the Femtosecond X‐ray Experiments (FXE) scientific instrument. This paper provides an overview of the currently implemented experimental baseline instrumentation and its performance during the commissioning phase, and a preview of planned improvements. FXE's versatile instrumentation combines the simultaneous application of forward X‐ray scattering and X‐ray spectroscopy techniques with femtosecond time resolution. These methods will eventually permit exploitation of wide‐angle X‐ray scattering studies and X‐ray emission spectroscopy, along with X‐ray absorption spectroscopy, including resonant inelastic X‐ray scattering and X‐ray Raman scattering. A suite of ultrafast optical lasers throughout the UV–visible and near‐IR ranges (extending up to mid‐IR in the near future) with pulse length down to 15 fs, synchronized to the X‐ray source, serve to initiate dynamic changes in the sample. Time‐delayed hard X‐ray pulses in the 5–20 keV range are used to probe the ensuing dynamic processes using the suite of X‐ray probe tools. FXE is equipped with a primary monochromator, a primary and secondary single‐shot spectrometer, and a timing tool to correct the residual timing jitter between laser and X‐ray pulses.